(3GdGYJQGa GdeJHGOd Hjf Cgd GdSfI hGdTjYI aj GdaJGhi hGdhKGFb GdJGQjNjI (B=s Mutual recognition between sunna and shia in fatwas and historical documents - (3GfUGQjGf, Ydjs ((3HjQhJ , dHfGf (B: s (3eQcR GdMVGQI dJfejI GdacQ GdESdGej,s, 2019)
(3GdGYJQGa GdeJHGOd, hJLfH GdJcajQ, hGdOYhI Edi GdhMOI, hJLfH Tb Uaha GdeSdejf, ef GdeaQOGJ GdJj cKQ JOGhdgG aj GdCOHjGJ GdESdGejI MJi cGOJ JUjQ ef HOjgjGJ GdNWGH GdESdGej aj aJQGJ YOI ef JGQjN CeJfG GdeYGUQ, hdcf eY GdCSa JfO Hjf GdajfI hGdajfI OYhI JUH aj YcS GdJjGQ GdWHjYj ddJLGQH GdLejdI GdJj YQaJgG GdCeI aJYhO GdMGLI Edi GdJPcjQ HGdeSdeGJ, hjYhO GdGTJZGd HJhVjM GdhGVMGJ hJYQja GdHOjgjGJ ef GdhGLHGJ GdeWdhHI ef GdYdeGA hGdeTJZdjf HGdYdhe GdESdGejI(B. (3hgPG GdcJGH gh eMGhdI ddJPcjQ hEYGOI JhKjb eLehYI ef GdeMWGJ GdhMOhjI, ef GdJGQjN GdESdGej GdeYGUQ ddYdGbGJ GdESdGejI GdESdGejI, hjZWj gPG GdcJGH eMWGJ YOI CgegG aJhi GdYdGeI GdTjN eMehO TdJhJ GdPj cGf dgG hbY ege aj eSGQ OYhI GdJbQjH Hjf GdePGgH GdESdGejI(B.s
(3JUeje GdZdGa (B: (3MSjf ehSi(B.s
Keywords: (3GdaJGhj GdTQYjIs; (3YdGbGJs -- (3Cgd GdSfIs; (3MhGQ GdCOjGfs